PENINGKATAN MOTIVASI BELAJAR MATEMATIKA MELALUI PENDEKATAN KONTEKSTUAL SISWA MTs PONDOK PESANTREN IBNUL QOYYIM PUTRA YOGYAKARTA - Sumargiyani, Sumargiyani (Jurnal Ilmiah AdMathEdu, 2011)
This study aims to improve Mathematics learning motivation through a contextual approach to students of MTs Ibnul Qoyyim sons boarding school Yogyakarta. This research is an action research. Setting of this research is 22 students of class Ia. Research planning is done for three cycles and completed in the second cycle. The first cycle consists of two meetings and the second cycle consists of two meetings. The data collected by the technique of diagnostic testing, observation sheet, questionnaire, interviews and documentation. The results of diagnostic tests on each cycle increased the average of learning results, which is from 78.48 in the cycle I to 84.02 in the cycle II. The results of student learning motivation questionnaire at the beginning of the meeting 65.22% included as the middle category. After done the learning by using the contextual approach, students learning motivation on cycle I are 74.44% and 75.56% in cycle II included as the high category. Based on questionnaire responses of students are 91.96% categorized as very interested. From observations and interviews result, it can be deduced that students respond positively to learning through contextual approach. So that, it can be concluded overall that learning through contextual approach can enhance students learning motivation MTs Ibnul Qoyyim sons boarding school Yogyakarta class Ia odd semester in academic year 2011/2012 with the subject of integers.